Prevalence and effect of cyberchondria on academic performance among undergraduate dental students: An institutional based study - Siva Kumar Patanapu; Chilukuri Sai Sreeja; Nagarani Veeraboina; Kandadi Vasavi Reddy; Sreenivas Voruganti; Patlola Anusha (Industrial Psychiatry Journal, 2022)
Background: Cyberchondria has been used to describe an increase in anxiety about one's health status as a result of excessive online searches. These online health research studies were associated with a small but reliable increase in depression and anxiety which may decrease concentration of a student on academics. Methods: The questionnaire was distributed among 302 undergraduate dental students (second year, third year, fourth year, and interns) of Kamineni Institute of Dental Sciences and Hospital. The survey tool comprised Cyberchondria Severity Scale–Short form (CSS-15) questionnaire and percentage of marks obtained in the previous University examination. Statistically significance was set at P < 0.05. Results: A significant difference was observed for subscale Compulsion (p = 0.05*), Distress (p = 0.001*) with a higher mean score among 24-26 years old dental students. Females had significant higher mean score subscales Distress (4.63 ± 2.93; P = 0.02*) and Reassurance (5.99 ± 2.90; P = 0.001*) than males. Regarding overall CSS, significant higher mean scores were observed among the students who scored less than 65% (7.90 ± 2.01) in their last year university academic examination (0.000*). Conclusion: Scheduling educational programs and strengthening easily accessible health services for the students has a particular importance in solving the health problems of young people.